Pengaruh Budaya Organisasi dan Komunikasi Terhadap Kinerja Karyawan Di Hotel Four Points By Sheraton Batam - Utami Tri Kinasih; Youmil Abrian; Yunus Supriharto (Departemen Pariwisata Universitas Negeri Padang, 2026)
This study investigates the impact of organisational culture and communication on employee performance at Four Points by Sheraton Batam. A quantitative methodology was adopted, utilising a causal-associative research design. Primary data were collected through a “Likert-scale questionnaire administered to a sample of 50 employees, selected via a saturation sampling technique. Subsequent data analysis was conducted using SPSS version 27, encompassing validity and reliability assessments, multiple linear regression, t-tests, F-tests, and the evaluation of the coefficient of determination. The empirical findings reveal that organisational culture and communication exert a positive and statistically significant influence on employee performance, both independently and simultaneously. Furthermore, the coefficient of determination demonstrates that these two independent variables explain 72,6% of the variance in employee performance, while the remaining 27,4% is attributable to exogenous factors beyond the scope of this investigation”. The results show that improving organisational culture and implementing effective communication can boost staff productivity. It is hoped that this research will assist hotel management in developing more efficient human resource management strategies to enhance organisational productivity and service quality.